Π-Stacking synthon repetitivity in coordination compounds. Issue 25 (24th May 2016) - Khavasi, Hamid Reza; Kavand, Sima
Abstract : The π-stacking synthon repetitivity in the crystal structures of HgX2 complexes of N -(1-chloro/bromo-naphthalen-4-yl)pyrazine-2-carboxamide ligands has been investigated. Structural analysis shows these compounds have almost the same propensity for the formation of π–π interactions in supramolecular crystal structures. Abstract : In this report, research on π-stacking synthon repetitivity and the effect of substituents in the crystal structures of HgX2 complexes of N -(1-chloro/bromo-naphthalen-4-yl)pyrazine-2-carboxamide ligands is described. Structural analysis shows that these compounds have almost the same propensity for the formation of π–π interactions in supramolecular crystal structures.